Feeding plate prosthesis for an infant with cleft lip and palate: a case report - Reddy, N Simhachalam; Sreenivasulu, Duggineni; Garlapati, Priyanka Reddy (International Journal of Dental Materials, 2023)
Cleft lip and palate are congenital anomalies that manifest at birth, leading to a range of complications such as feeding challenges, dysfunction of the eustachian tube, middle ear infections and effusion, hearing loss, speech disorders, and dental and orthodontic issues. A feeding plate is a prosthetic solution crafted to address these challenges by effectively sealing the cleft and restoring the separation between the oral and nasal cavities. This case report details the procedure for fabricating a feeding plate specifically designed for neonates with cleft lip and palate.